Respon Pertumbuhan dan Hasil Microgreens Beberapa Varietas Tanaman Caisim (Brassica juncea L.) pada Berbagai Jarak Tanam - Ubaedillah, Hafifah; Rahayu, Yayu Sri; Supriadi, Devie Rienzani; Rohaeni, Wage Ratna (Paspalum: Jurnal Ilmiah Pertanian, 2024)
The diminishing amount of land available for agriculture and the growing demand for nutritious food have made it necessary to find alternative sources of fresh vegetables. Urban farming, especially the cultivation of microgreens, can help meet this demand. Microgreens offer several advantages, such as time and cost savings, and they require minimal space while growing quickly. However, the optimal spacing for different types of microgreens is not extensively documented, as research on microgreens is still limited in Indonesia. The Brassicaceae family is one of the most commonly cultivated families for microgreens. This study was carried out at Room A, Faculty of Agriculture, Singaperbangsa Karawang University, Campus 2. The experimental method used was a factorial randomized block design (RBD Factorials) with two treatments for varieties and three for spacing, repeated five times, resulting in 30 experimental units. Factor I, Varieties, consisted of v1 (Tosakan) and v2 (Shinta). Factor II, Spacing, consisted of j1 (1 cm x 1 cm), j2 (1 cm x 2 cm), and j3 (2 cm x 2 cm). The data were analyzed using an analysis of variance (Uji F) at a 5% level. If the results of the analysis of variance were significantly different, the study continued with a multiple range test (DMRT) at a 5% level to determine the best-performing treatment. There was an interaction between the treatments for microgreen varieties and spacing on parameters such as plant density, dry weight of the plant, and fresh weight. There was a significant effect of the variety on the parameter of chlorophyll content, and a significant effect of spacing on the parameters of plant growth rate and the age of leaf appearance. Additional types of plants are needed to determine significant differences related to spacing and their interactions.